Milk Production and Evaluation in Farms Raised Anatolian Water Buffalo (Bubalus bubalis); A Case Study of Igdir Province - Yilmaz, I; Yurt, B.; Sahin, O. (Hellenic Veterinary Medical Soc, 2023)
This study conducted a questionnaire with 98 enterprise owners rearing Anatolian water buffalo in 2018 in Igdir city of Turkey. The average daily milk yield, annual milk yield, and sales price of buffalos milk of the enterpris-es were determined as 5.48 +/- 0.07 (kg), 1228.56 +/- 15.60 (kg/lactation), and USD1.06 (price/per kg), respectively. At the same time, 3.0% of the produced raw milk was put on the market as raw milk, 20.90% as product, and 76.10% as raw milk + product. Therewithal, 81.54% of the processed milk was marketed as butter+cream+curd cheese, 7.69% as but-ter + cheese + curd cheese, and 10.77% is marketed as butter + cheese + yoghurt + curd cheese. It was determined that out of the companies selling raw milk, 88.70% sold to street milk + grocery stores, and 11.30% sold to dairy farms. As a result, to ensure sustainable buffalo breeding in Igdir province, buffalo milk collection centers, processing facilities, and buffalo breeders' association should be established. There is need to protect Anatolian water buffaloes reared in Igdir province as genetic resources crossbreeding with other buffalo breeds should not be allowed. It should be remembered that animals adapt to their environment after many years. Matings made to increase the amount of milk can negatively affect the properties like butter and cream yield. However, inbreeding of animals raised in the province should not be allowed. Cows must be mated according to a system.
Keywords: Water buffalo; farms; milk production; evaluation; marketing